ANALISIS PROBLEM PEMBIAYAAN MUDHARABAH SERTA SOLUSINYA - Sarono, Agus (Fakultas Hukum, Universitas Diponegoro, 2019)
ABSTRACT Islamic banks were originally constructed as a system with profit and loss sharing in all its operational mechanism. The problem then was the product of this need honesty in its process. It is very difficult to be controlled. Costumers more understand the process and the appication of the profit-sharing agreement than Syariah Bank its self. This causes problems and deviation of profit-sharing system by costomer. This paper will try to discuss about problems and solutions sharing system (mudharabah) in a financing scheme in Islamic banks